(untitled) (SCIÉNDO INGENIUM, 2022)
In this research with the help of Neuroscience, Physiology, Biochemistry and Molecular Biology, thought was analyzed as movement, creation or product of brain neurons, which allows differentiating Law from legal sciences and the institutions with which they interrelate, as a product of an individual thought of each human being. The objective was to define and structure the levels and dimensions of human thought for the science of law and legal sciences, throughout the history of humanity. The scientific method was applied as the main method and the hermeneutical interpretation as a technique, in order to focus linguistics on the technical use of the object of study and its significance in law, legal sciences and legal-constitutional institutions. It was concluded that thought is a spatio-temporal movement of the brain neurons of living beings, it materializes as a human system, depending on the processes of hominization and humanization of man, in nature, in society, at work in direct relationship with the cosmos. We report the bibliography that served us as a basis.